2017
DOI: 10.3389/fimmu.2017.01812
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Nanoparticles That Promote Tumor Necrosis Factor Receptor 2 Expressing Regulatory T Cells in the Lung and Resistance to Allergic Airways Inflammation

Abstract: Synthetic glycine coated 50 nm polystyrene nanoparticles (NP) (PS50G), unlike ambient NP, do not promote pulmonary inflammation, but instead, render lungs resistant to the development of allergic airway inflammation. In this study, we show that PS50G modulate the frequency and phenotype of regulatory T cells (Treg) in the lung, specifically increasing the proportion of tumor necrosis factor 2 (TNFR2) expressing Treg. Mice pre-exposed to PS50G, which were sensitized and then challenged with an allergen a month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Recent results indicated that T regs are progressively and specifically accumulated in lung tissue of mice treated with silica where they promote pulmonary immunosuppression and fibrosis ( 58 , 60 ) (Figure 2 ). This hallmark of immunological tolerance and immunosuppressive environment was observed with other particles, detected locally and systemically, and induced by the Wnt/B-catenin pathway ( 57 , 59 , 97 , 98 ). Lung T regs directly stimulated fibroblast proliferation and collagen deposition after transfer in non-treated mice ( 58 ).…”
Section: Contribution Of Regulatory T and B Lymphocytes In Response Tmentioning
confidence: 62%
See 1 more Smart Citation
“…Recent results indicated that T regs are progressively and specifically accumulated in lung tissue of mice treated with silica where they promote pulmonary immunosuppression and fibrosis ( 58 , 60 ) (Figure 2 ). This hallmark of immunological tolerance and immunosuppressive environment was observed with other particles, detected locally and systemically, and induced by the Wnt/B-catenin pathway ( 57 , 59 , 97 , 98 ). Lung T regs directly stimulated fibroblast proliferation and collagen deposition after transfer in non-treated mice ( 58 ).…”
Section: Contribution Of Regulatory T and B Lymphocytes In Response Tmentioning
confidence: 62%
“…CNT induce the expression of TGF-β and IL-10 ( 57 ) as observed for micrometric silica (see above). Nanoparticles also facilitate polarization of immunosuppressive T regs and anti-inflammatory Th2 lymphocytes ( 98 , 123 , 124 ). Mechanistic studies investigating the effects of nanoparticles on T-lymphocyte immunosuppressive lineage commitment revealed that nanoparticles (carbon, grapheme, and iron) directly interfere with autophagy, ROS production, NFκB-nuclear translocation or antigen processing by dendritic cells ( 124 126 ).…”
Section: Nanoparticles Induce Immunosuppressionmentioning
confidence: 99%
“…Previously, it was shown that TNFR2 maintains adequate IL-12 production by DCs in inflammatory responses by regulating endogenous TNF level ( 91 ). In addition, selective expansion of maximally suppressive TNFR2 + Foxp3 + Tregs in pulmonary inflammation can be induced by engineered nanoparticles through the activation of CD103 + DCs ( 92 ).…”
Section: Pathogenic Role Of Tnf In Allergic Manifestationmentioning
confidence: 99%
“…Nanoparticles, with their various immunological effects in the lung ( 109 ), can be utilized to selectively block TNFR1 and/or activate TNFR2. A synthetic nanoparticle has been used to imprint innate immunity when pre-exposed mice preferentially expanded TNFR2 + Foxp3 + Tregs after allergen challenge, partly via the activation of CD103 + DCs ( 92 , 110 ). This non-toxic engineered nanoparticle evidenced the selective modulation of Tregs homeostasis through mechanisms such as maintenance of TNF-TNFR2 interaction, targeting CD103 + DCs, and expanding the proliferative rate of Tregs, thus decreasing the susceptibility to allergic disease.…”
Section: Therapeutic Targeting Of Tnf-tnfr2 In Allergymentioning
confidence: 99%
“…Despite the emerging trends of using nanoparticles in immunotherapy, no studies have investigated any type of nanocarriers to target TNFR2 on cancer cells. However, based on some previous novel reports about the effects of nanoparticles on immune homeostasis [13], especially using nanoparticles to promote TNFR2 + Foxp3 + regulatory T cells (Tregs) in inflammatory models [14,15], we have suggested in our recent perspective review the possibility of blocking TNF-TNFR2 axis via nanoparticles [16].…”
mentioning
confidence: 99%